Mechanical properties of hybrid composites with alternately woven carbon/glass fibers on stainless steel wire mesh - Venkat Ramanan A; Rajamurugan G (Results in Engineering)
Synthetic fiber-reinforced composites are widely used in engineering applications because of their superior mechanical properties. However, delamination remains a critical limitation that reduces structural integrity and long-term performance. This study investigates the enhancement of interlaminar strength and mechanical performance through the integration of stainless-steel wire mesh (SSWM) with carbon fiber (CF) and glass fiber (GF) yarns in hybrid composite structures. Four types of composite laminates were fabricated using the hand lay-up method: (1) plain woven CF yarn on SSWM (CWC), (2) alternately woven CF/GF yarn on SSWM (CWAC), (3) plain woven GF yarn on SSWM (GWG), and (4) alternately woven CF/GF yarn on SSWM (GWAG). All were bonded with matrix materials such as epoxy resin and hardener. Mechanical testing revealed a significant improvement in the tensile strength of both the CWAC and GWAG composites. CWAC exhibited an increase of 265.02 MPa, while GWAG showed a 255.49 MPa enhancement. Flexural strength also improved notably, with CWAC and GWAG recording increases of 385.04 MPa and 368.92 MPa, respectively. Additionally, the CWAC exhibited an impact strength enhancement of 11.5 J, highlighting its superior load-bearing capability. Fractography using Field Emission Scanning Electron Microscopy (FESEM) revealed evidence of fiber breakage and brittle matrix fractures. Furthermore, X-ray Diffraction (XRD) analysis confirmed a synergistic interaction among CF, GF, and SSWM, which contributed to the overall improvement in structural performance. The effectiveness of alternate CF/GF weaving on SSWM as a practical method to reduce delamination and enhance the mechanical behavior of hybrid composites for demanding engineering applications.